2022
DOI: 10.1186/s12871-022-01605-9
|View full text |Cite
|
Sign up to set email alerts
|

Reported definitions of intraoperative hypotension in adults undergoing non-cardiac surgery under general anaesthesia: a review

Abstract: Background Intraoperative hypotension (IOH) during non-cardiac surgery is common and associated with major adverse kidney, neurological and cardiac events and even death. Given that IOH is a modifiable risk factor for the mitigation of postoperative complications, it is imperative to generate a precise definition for IOH to facilitate strategies for avoiding or treating its occurrence. Moreover, a universal and consensus definition of IOH may also facilitate the application of novel and emergin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 52 publications
(53 reference statements)
0
19
0
Order By: Relevance
“…Bijker et al [ 49 ] identified 140 definitions of IOH after a review of 130 articles. The most used definition of IOH was as follows: a decrease in the systolic BP of more than 20% from the baseline BP or a MAP < 65 mmHg [ 50 , 51 ]. The latter, also known as absolute thresholds, is used more frequently for the following reasons: (1) baseline BP measurements are often unknown, and approximately one-third of patients do not have a baseline BP value preoperatively, as described by Monk et al [ 28 ]; (2) relative thresholds are not superior to absolute thresholds in predicting unfavorable outcomes as reported by Salmasi et al [ 52 ] in a large-sample retrospective cohort analysis; (3) absolute thresholds are concrete and easier to use in decision-making; and (4) preoperative BP measurements are often elevated due to tension and anxiety.…”
Section: Intraoperative Bp Control Target and Its Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bijker et al [ 49 ] identified 140 definitions of IOH after a review of 130 articles. The most used definition of IOH was as follows: a decrease in the systolic BP of more than 20% from the baseline BP or a MAP < 65 mmHg [ 50 , 51 ]. The latter, also known as absolute thresholds, is used more frequently for the following reasons: (1) baseline BP measurements are often unknown, and approximately one-third of patients do not have a baseline BP value preoperatively, as described by Monk et al [ 28 ]; (2) relative thresholds are not superior to absolute thresholds in predicting unfavorable outcomes as reported by Salmasi et al [ 52 ] in a large-sample retrospective cohort analysis; (3) absolute thresholds are concrete and easier to use in decision-making; and (4) preoperative BP measurements are often elevated due to tension and anxiety.…”
Section: Intraoperative Bp Control Target and Its Implicationsmentioning
confidence: 99%
“…Several studies [ 16 , 28 , 52 76 ] found that IOH was associated with postoperative detrimental outcomes (such as AKI, myocardial injury, and neurocognitive disorders), which is related to the duration and magnitude of hypotension [ 77 ], suggesting that IOH should be avoided perioperatively ( Table 1 ). Based on existing evidence [ 51 , 56 , 58 , 74 , 75 ], intraoperative MAP should be maintained above 65 mmHg in normal adult patients, and in patients with other comorbidities (for example, coronary artery disease and carotid stenosis), the intraoperative MAP must be individualized based on the patient's pathophysiology and clinical situation. For example, the MAP of patients with chronic hypertension should be maintained above 70 mmHg.…”
Section: Intraoperative Bp Control Target and Its Implicationsmentioning
confidence: 99%
“…Evidence has demonstrated that longer periods of SBP < 100 mmHg following non-cardiac surgery are related with an increased risk of organ damage and death ( Sessler et al, 2019 ). Based on Weinberg et al (2022) , 153 studies (48.1%) did not include any duration variable in the definition of hypotension; however, IOH should be defined using the absolute values indicated in the POQI statement ( Sessler et al, 2019 ); that is, MAP < 60–70 mmHg or SBP < 100 mmHg. Accordingly, we defined IOH as SBP < 100 mmHg in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of IOH remains controversial ( Filiberto et al, 2021 ). Based on the Perioperative Quality Initiative (POQI) statement ( Sessler et al, 2019 ) and related studies, we defined IOH as a SBP < 100 mmHg ( Weinberg et al, 2022 ). As primary endpoints, a composite measure of IOH incidence, including frequency, absolute duration, and relative duration (percentage of total anaesthesia time), was established for this investigation, as stated by Schneck et al (2020) , while secondary endpoints included the pain score recorded 60 min after surgery and perioperative sufentanil dose.…”
Section: Methodsmentioning
confidence: 99%
“…IOH has been reported in 5-99% of surgical cases. 3,24,25 Limiting to studies that use a similar MAP threshold of 65 mmHg, the incidence of IOH ranges from 19-88% for MAP < 65 mmHg for at least 1 minute, 3,8,26 45-49% for at least 5 minutes, 3,26 and 31% for at least 10 minutes. 3,26 Most previous studies are from major academic institutions.…”
Section: Discussionmentioning
confidence: 99%